Validation of the Social Media Disorder Scale using network analysis in a large representative sample of Czech adolescents - Šablatúrová, Nika; Rečka, Karel; Blinka, Lukas (Frontiers in Public Health, 2022)
Background: The importance of studying the excessive use of social media in current adolescents is increasing. So is the need for in-depth evaluations of the psychometric properties of the measurement tools. This study investigates the properties of the Social Media Disorder Scale (SMDS; 1) in a large representative sample of Czech adolescents. Methods: We analyze a representative sample of 13,377 Czech adolescents (50.9% boys), 11–16 years old, who participated in the Health Behaviour in School-aged Children (HBSC) survey (2017-18), using confirmatory factor analysis (CFA) and network models. Furthermore, we evaluate the measurement invariance and construct the validity of the SMDS. Results: We found support for a single dominant factor, but not for strict unidimensionality. Several residual correlations were identified. The strongest were for: problems–conflicts–deceptions; persistence–escape; and preoccupation-tolerance-withdrawal. Girls, particularly 13- and 15-year-olds, scored higher than boys in the same age group, and 13- and 15-year-olds scored higher than 11-year-olds, although some items were not invariant between the groups. The SMDS was positively related to other online activities, screen time, and falling asleep late, and negatively related to well-being and mental health. Discussion and Conclusions: The SMDS showed solid psychometric properties and construct validity. However, small violations of measurement invariance were detected. Furthermore, the network analysis showed important residual relationships between the items.